O PCB e a ruptura da tradição: dos impasses das formulações do exílio ao exílio da política no Brasil (1971-1991) - Souza, José Milton Pinheiro de (2014)
The main objective of this thesis in to unraveling the pathways that led to the great political and organizational crisis of PCB in the late 1980s. To this end, we sought investigate, with the focus on the period 1971-1991, as the PCB, in the search for space of formal democracy, broke with its historic tradition of struggle and submitted the working class in its wide range of theoretical and political interpretation. Our raised hypothesis is that policy formulations developed by leading core stagnant (CC), which was mostly exiled on account of bourgeoismilitary dictatorship, led the PCB to the exile of political during Brazilian long democratic transition. This party, political operator built for defends the political and social program of the proletariat, succumbed to the legality of the bourgeois order by virtue of their formulations and subaltern political practice developed by his direction during the studied period. Its analytical framework was inherited from of March Declaration (1958) and helped to defeat the party during the political process of transition from the bourgeois-military dictatorship to the formal (bourgeois) democracy